2008
DOI: 10.1111/j.1468-1293.2008.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing strategies across European countries

Abstract: With universal access to effective combination antiretroviral therapy (ART), people in need can gain effective treatment but are only able to benefit from these advances if they are aware of their serostatus and have effectively accessed testing services. Despite the expectation that ART would lead individuals to seek earlier testing, this trend has not been observed in practice, with stable or even increasing rates of late diagnosis in Europe being witnessed. Ahead of a gathering of key European stakeholders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 7 publications
1
73
0
Order By: Relevance
“…Frequency of needle sharing in the East is more varied, ranging between 2% and 79% [48,85] and in Russia alone between 8% and 79% [85,91]. The estimate of 2% from Vilnius, Lithuania, refers to receptive sharing in the past four weeks [48], and most estimates range between 20% and 30%, with one study estimating sharing (receptive or distributive) in the past 30 days at 98% [92].…”
Section: Needle/syringe Sharingmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequency of needle sharing in the East is more varied, ranging between 2% and 79% [48,85] and in Russia alone between 8% and 79% [85,91]. The estimate of 2% from Vilnius, Lithuania, refers to receptive sharing in the past four weeks [48], and most estimates range between 20% and 30%, with one study estimating sharing (receptive or distributive) in the past 30 days at 98% [92].…”
Section: Needle/syringe Sharingmentioning
confidence: 99%
“…Standardized indicators are currently lacking across the region. An important finding of the review is that access to mainstream sexual health provision for MSM can be impeded by staff hostility borne out of the dual stigma of homosexuality and HIV, and patient fears concerning breaches of confidentiality [90][91][92]. Such concerns appear more acute in the East.…”
Section: Strengthening Hiv Prevention Among Msmmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have also identified clinical (previous sexually transmitted infections or history of HIV testing) and organizational factors that are associated with HIV testing [8][9][10]. In addition, social factors such as HIV-related stigmatization or discrimination have been proposed [10]. A recent meta-analysis comparing high-and low-income countries revealed that despite the many differences between the two locations, risky behaviors and stigmatization constitute universal determinants of HIV testing [11].…”
Section: Introductionmentioning
confidence: 99%
“…These are generally followed by individual factors such as risky behaviors for HIV, perceptions of HIV risk, and knowledge about HIV [7][8][9]. A few studies have also identified clinical (previous sexually transmitted infections or history of HIV testing) and organizational factors that are associated with HIV testing [8][9][10]. In addition, social factors such as HIV-related stigmatization or discrimination have been proposed [10].…”
Section: Introductionmentioning
confidence: 99%